RANCANG BANGUN BAGIAN PNEUMATIK MESIN PEWARNA BENANG TENUN IKAT SEMI OTOMATIS: DESIGN AND CONSTRUCTION OF PNEUMATIC PARTS SEMI-AUTOMATIC TIED WEAVING YARN DYES MACHINE - Mutiara Bahtiar, Ahmad Dony; Hendarti, Devina Rosa; Cahyono, Hiding; Setiawan, Deny (Jurnal Teknik Mesin, 2022)
To Increase production woven fabric and efficiency production woven fabric, which can alternatives realizing an increase it by create a Design Machine Coloring Yarn Weaving. Design method Machine Coloring Yarn Weaving Using a pneumatic system and electric motor as a driven source, includes design planning, design elements of machine (machine frame, color liquid container, twist yarn weaving, pulley, v-belt and pneumatic systems). Coloring Machine Yarn Weaving semi automatic pneumatic section use pneumatic piston diameter of 32 mm and air requirements needed 0.000746m3/s.